Usefulness of routine assessment of free testosterone for the diagnosis of functional male hypogonadism. (31st December 2022) - Facondo, Paolo; Di Lodovico, Elena; Pezzaioli, Letizia Chiara; Cappelli, Carlo; Ferlin, Alberto; Delbarba, Andrea
Abstract: Objective: To investigate whether routine assessment of free testosterone improves the diagnostic accuracy of functional hypogonadism. Methods: Total and free testosterone (calculated on SHBG levels) were determined in 188 patients with sexual symptoms and 184 with infertility. Results: Hypogonadism (calculated free testosterone <63 pg/ml) was found in 47/188 (25.0%) patients with sexual symptoms and in 21/184 (11.4%) with infertility. Total testosterone determination misdiagnosed hypogonadism in 8.4% (12/143) of men with sexual symptoms and in 2% (3/152) with infertility. In subjects with borderline total testosterone, only 24.7% (19/77) had hypogonadism confirmed by free testosterone levels. Free testosterone levels significantly correlated with age, haematocrit, gonadotropins, gynecomastia, BMI, and number of co-morbidities, whereas total testosterone associated only with the latter two. Furthermore, age, haematocrit, BMI, and the presence of erectile dysfunction and of low libido were significantly different between men with normal and low free testosterone, whereas only BMI and low libido were significantly different between patients with normal and low total testosterone. Conclusion: Routine assessment of free testosterone allows a more accurate diagnosis of functional hypogonadism, especially in men with sexual symptoms. Free testosterone levels associate with clinical and biochemical parameters of androgen deficiency better than total testosterone levels.